More Is Better: Recent Progress in Multi-Omics Data Integration Methods - Huang, Sijia; Chaudhary, Kumardeep; Garmire, Lana X. (Frontiers in Genetics, 2017)
Multi-omics data integration is one of the major challenges in the era of precision medicine. Considerable work has been done with the advent of high-throughput studies, which have enabled the data access for downstream analyses. To improve the clinical outcome prediction, a gamut of software tools has been developed. This review outlines the progress done in the field of multi-omics integration and comprehensive tools developed so far in this field. Further, we discuss the integration methods to predict patient survival at the end of the review.